Pendidikan Kesetaraan Gender dalam Pengasuhan Anak Sebuah Analisis dari Perspektif Islam - Aini, Kurrota (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2024)
This study focuses on the importance of gender equality education for children from an Islamic perspective, emphasizing education towards the formation of understanding, attitudes, and behaviors that support gender equality and justice from an early age. This research uses a literature study method, aiming to explore how Islamic teachings in the Quran and Hadith provide a strong foundation for promoting gender equality, challenging stereotypes and gender discrimination, and supporting the development of each individual's potential without gender distinction. The findings indicate that gender equality education facilitates children in fully exploring and developing their potential, reducing gender-based discrimination and violence, and supporting children's mental health and well-being. This gender equality education also prepares children to participate equally in all aspects of life. From an Islamic perspective, gender equality education not only supports the intellectual, spiritual, and moral development of children but also emphasizes the importance of equality and justice between men and women. This research highlights the forms of gender education for children recommended in Islam, including the teaching of fundamental Islamic values such as mutual respect, empathy, and cooperation, and the integration of these values into daily life. It demonstrates that gender equality education in Islam can bridge tradition and modernity, enabling the younger generation to appreciate traditional wisdom while applying principles of equality and social justice. This study provides significant insights into how gender equality education can shape a more just and equal society.